1996
DOI: 10.1046/j.1464-410x.1996.86017.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical activity of the corpus cavernosum in patients with corporal veno‐occlusive dysfunction

Abstract: The pattern of discoordination diagnosed by electromyography after injection with papaverine may explain some aspects of VOD and highlights the importance of performing electromyography of the corpus cavernosum in the diagnostic evaluation of VOD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 2 publications
3
22
0
2
Order By: Relevance
“…We used strict selection criteria and found especially subjectively high success rates with a mean follow–up of 28 months (range 4–42) and observed minimal decreases in success rates with time. We know that electromyographic abnormalities were observed more frequently in patients with COD [8]. We also observed high CO and autonomic dysfunction rates in young patients [9].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We used strict selection criteria and found especially subjectively high success rates with a mean follow–up of 28 months (range 4–42) and observed minimal decreases in success rates with time. We know that electromyographic abnormalities were observed more frequently in patients with COD [8]. We also observed high CO and autonomic dysfunction rates in young patients [9].…”
Section: Discussionmentioning
confidence: 91%
“…The speed of the thermowriter paper was 5 mm/s. Measurement of the electrical activity of corpus cavernosum was done for 10 min using coaxial electrodes during the flaccid state and after intracavernous papaverine (60 mg) injection [8]. Our maximum intracavernous papaverine dose was 120 mg.…”
Section: Methodsmentioning
confidence: 99%
“…C¸olakoglu et al 17 likewise considered that cavernosometry can give rise to false-positive readings in patients with intrinsic cavernous muscle damage, only detectable by CC-EMG. Kayigil et al 18 in turn compared the penile Doppler ultrasound findings, cavernosometry, and CC-EMG. These authors showed that subjects with venous leakage present penile arterial insufficiency or persistence of the potentials of the corpora cavernosa in the CC-EMG recordings.…”
Section: Inferential Statisticsmentioning
confidence: 99%
“…This lack of relaxation may be due to anxiety-induced elevation of the sympathetic tone. 18 In another five cases, the lack of erectile response would be of a mixed cause: lack of erectile tissue relaxation and arterial insufficiency.…”
mentioning
confidence: 98%
“…On the other hand, CC-EMG gives information about cavernosal smooth muscle tone, the relaxation ability of cavernosal muscle, or the existence of autonomic dysfunction [22][23][24].…”
Section: © 2 0 11 T H E a U T H O R S 11 2 B J U I N T E R N A T I O mentioning
confidence: 99%